IRAS 16475–4609: A Young Compact H II Region Sculpting its Molecular Environment - Felipe Navarete; Sean D. Points; Augusto Damineli (The Astronomical Journal)
We present a near-infrared spectroscopic and imaging analysis of the star-forming region IRAS 16475−4609, based on TripleSpec/SOAR spectroscopy and NEWFIRM/CTIO imaging, complemented by archival radio and submillimeter data. Our spectroscopic analysis indicates that the central source is an early B-type star (B0–B0.7 V) powering a compact H ii region characterized by strong H i and He i recombination lines, and molecular H _2 emission. We derive a distance of 3.51 ± 0.74 kpc, consistent with the position of the Scutum–Crux near arm at a Galactic longitude of ∼340 ^∘ . At this distance, the ionized gas traced by Br γ emission has a radius of 0.27 ± 0.06 pc, placing the source in a transition phase between ultracompact and compact H ii regions. From radio data, we estimate an ionizing photon flux of N _Ly = (2.3 ± 0.3) × 10 ^47 photons s ^−1 , and an electron temperature of T _e = (5.4 ± 0.2) × 10 ^3 K for the ionized gas. The analysis also reveals an obscured high-density molecular clump SW of the H ii region, coincident with an ATLASGAL submillimeter peak, indicating a potential site of ongoing and triggered star formation as the ionization front advances into the surrounding molecular material. These results suggest that IRAS 16475−4609 is a young high-mass star-forming region with stellar feedback actively shaping its environment, offering valuable insight into the early evolution of compact H ii regions.